2008
DOI: 10.1021/jp7096668
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemistry Investigation on Protein Protection by Alkanethiol Self-Assembled Monolayers against Urea Impact

Abstract: The present investigation reports the electrochemical measurements of azurin (Az) adsorbed on a series of alkanethiol self-assembled monolayers (SAMs) under the influence of urea molecules. Theoretical fitting with the Marcus model obtains the electron-transfer rate constant, k et , and the reorganization energy, λ. When the underlying SAM is longer than 10 methylene units, k et shows an obvious chain-length dependence from which an electron-tunneling coefficient, β, of 1.09 per methylene is deduced. Combined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

8
65
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(75 citation statements)
references
References 99 publications
8
65
2
Order By: Relevance
“…Previous studies that exploited SAM-coated electrodes revealed two kinds of phenomenological behavior (17)(18)(19)(20)(21)(22)(24)(25)(26)(27)(28)(29)(30)(31). For the case of thicker SAMs (long-range ET), these studies showed an exponential decay of k et with the SAM thickness (that is a part of the ET distance, R e ); in accordance with the nonadiabatic ET (tunneling) theory (1, 3, 17-22, 24-32, 46-50):…”
supporting
confidence: 74%
See 4 more Smart Citations
“…Previous studies that exploited SAM-coated electrodes revealed two kinds of phenomenological behavior (17)(18)(19)(20)(21)(22)(24)(25)(26)(27)(28)(29)(30)(31). For the case of thicker SAMs (long-range ET), these studies showed an exponential decay of k et with the SAM thickness (that is a part of the ET distance, R e ); in accordance with the nonadiabatic ET (tunneling) theory (1, 3, 17-22, 24-32, 46-50):…”
supporting
confidence: 74%
“…According to earlier work (19,20,25,26,30,31), Az can be immobilized by the interaction of its hydrophobic patch with the hydrophobic CH 3 -terminal groups of the SAM of the general type:…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations